Taxonomic study of Oxalis section Thamnoxys (Oxalidaceae) in Brazil - Maria Carolina de Abreu; Ykaro Richard Oliveira; Juliana Silva dos Santos; Reginaldo Carvalho; Marcos José da Silva; Margareth Ferreira de Sales (Rodriguésia)
Abstract Oxalis comprises ca. 500 species and has a tropical and subtropical distribution. This genus contains four subgenera and Oxalis subg. Thamnoxys is the most diverse in Brazil. This subgenus has 9 sections, of which section Thamnoxys is the most diverse with 28 species. This work is based on a taxonomic study of Oxalis section Thamnoxys in Brazil and includes descriptions, illustrations, and notes for the recorded species. The following species were recorded: Oxalis barrelieri, O. cerradoana, O. clausenii, O. cratensis, O. cytisoides, O. diamantinae, O. divaricata, O. frutescens, O. hedysarifolia, O. hyalotricha, O. jacobinensis, O. mucronulata, O. nigrescens, O. pilulifera, O. pyrenea, O. renifolia, O. sellowii, O. sepium, and O. suborbiculata. These species are mostly distributed in rainforest and seasonal semi-deciduous forest.